Um estudo meta-avaliativo de uma experiência de auto-avaliação em uma Instituição de Educação Superior - Gimenes, Nelson Antonio Simão (2006)
With the objective to analyze the process of auto-evaluation developed in an Institute of Higher Learning in the interior of the state of São Paulo, we carried out a meta-evaluation from the point of view of the coordinators in the area of biological-health of the institution that is being used for the study utilizing an instrument of meta-evaluation, based on the standards of Utility and Accuracy developed by the Joint Committee on Standards for Educational Evaluation and made based on a free adaptation of the Program Evaluation Models Meta-evaluation Checklist. There was a main concern, during this work, of reflecting on the public policies of evaluation, not as one more legal demand of institutions in relation to the responsible government authorities, but as a procedure able to generate essential information for Institutions of Higher Learning, with the intention of contributing to its improvement and institutional development. The results show that although the autoevaluation carried out at the Institution of Higher Learning has been, in the opinion of the respondents, satisfactory; we identified some problems, especially concerning the difficulties of the internal evaluation of promoting adequate conditions for the generation of institutional improvements; as well as the effective involvement of the community from the perspective of amplified participation. We believe this study can contribute in the debate over the role of auto-evaluation and the importance of it in the improvement of the System of Higher Learning in Brazil, as well as reflecting on the adequate standards for the development of evaluative processes that generate changes and improvements on and for the different sectors of an Institution of Higher Learning, such as teaching, research, complementary activities and management, overpassing the legal-bureaucratic demands of the regulatory agencies of this system. Finally, we believe that to overcome these problems it is necessary to develop various and efficient forms of access, dissemination and feedback of the information collected during the evaluative process, which would make possible an improved comprehension of the objectives for the different segments of the local academic community